Accuracy of Micro-Computed Tomography in Post-mortem Evaluation of Fetal Congenital Heart Disease. Comparison Between Post-mortem Micro-CT and Conventional Autopsy. - Sandrini, Camilla; Rossetti, Lucia; Zambelli, Vanessa; Zanarotti, Roberta; Bettinazzi, Franca; Soldá, Roberta; Di Pace, Concetta; Hoxha, Stiljan; Ribichini, Flavio Luciano; Faggian, Giuseppe; Lombardi, Claudio; Luciani, Giovanni Battista (Frontiers in Pediatrics, 2019)
Aims: Early prenatal diagnosis of congenital heart disease is feasible. Conventional autopsy is the current gold standard method for post-mortem confirmation. Radiologic techniques alternative to conventional autopsy, such as post-mortem micro-computed tomography, have been proposed in case of limited diagnostic accuracy (i.e. early termination of pregnancy, samples of small dimension or of low weight). The aim of the present study was to define accuracy of micro-computed tomography for post-mortem diagnosis of congenital heart disease in gross anatomy samples. Methods and results: Fetal heart underwent in-utero prenatal echocardiography and ex-vivo post-mortem evaluation by 9 µm resolution micro-computed tomography and conventional autopsy. For each case, 25 indices of cardiac anatomy were studied by post-mortem micro-computed tomography and conventional autopsy; these were used to compare the two post mortem techniques. Ten samples were examined (gestational age between 12+4 and 21+6 weeks of gestation). Considering comparable indices, agreement between post-mortem micro-computed tomography and conventional autopsy was of 100% and sensitivity and specificity were of 100%. In “challenging specimens”, post-mortem micro-computed tomography diagnoses more indices as compared to conventional autopsy and 84% of “not-diagnostic” indices at conventional autopsy would be diagnostic at post-mortem micro-computed tomography. Conclusion: Micro-computed tomography can be a valid diagnostic alternative to conventional autopsy for post-mortem evaluation of human fetal heart. In addition, it may prove superior to conventional autopsy particularly in cases coming from early termination of pregnancy or in samples of small dimension or of low weight.